Environmental contaminants perturb fragile protein assemblies and inhibit normal protein function - Lawrence, Sarah H. (2013)
The molecular mechanisms whereby small molecules that contaminate our environment cause physiological effects are largely unknown, in terms of both targets and mechanisms. The essential human enzyme porphobilinogen synthase (HsPBGS, a.k.a. 5-aminolevulinate dehydratase, ALAD) functions in heme biosynthesis. HsPBGS catalytic activity is regulated allosterically via an equilibrium of inactive hexamers and active octamers, and we have shown that certain drugs and drug-like small molecules can inhibit HsPBGS in vitro by stabilizing the hexamer. Here we address whether components of the National Toxicology Program library of environmental contaminants can stabilize the HsPBGS hexamer and inhibit activity in vitro. Native polyacrylamide gel electrophoresis was used to screen the library (1,408 compounds) for components that alter the oligomeric distribution of HsPBGS. Freshly purchased samples of 37 preliminary hits were used to confirm the electrophoretic results and to determine the dose-dependence of the perturbation of oligomeric distribution. Seventeen compounds were identified which alter the oligomeric distribution toward the hexamer and also inhibit HsPBGS catalytic activity, including the most potent HsPBGS inhibitor yet characterized (Mutagen X, IC(50) = 1.4 μM). PBGS dysfunction is associated with the inborn error of metabolism know as ALAD porphyria and with lead poisoning. The identified hexamer-stabilizing inhibitors could potentiate these diseases. Allosteric regulation of activity via an equilibrium of alternate oligomers has been proposed for many proteins. Based on the precedent set herein, perturbation of these oligomeric equilibria by small molecules (such as environmental contaminants) can be considered as a mechanism of toxicity.